2012
DOI: 10.1246/cl.2012.1232
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Dynamic Receding Contact Angles Studied during the Flow of Dilute Aqueous Surfactant Solutions through Fluorinated Microtubes

Abstract: We report on the time-dependent dewetting behavior of dilute surfactant solutions of hexadecyltrimethylammonium bromide (CTAB) during forced flow in fluorinated ethylene propylene (FEP) microtubes. The dynamic receding contact angle of the solution at a given velocity decreased as the solid liquid contact time increased. Kinetics with long relaxation time of several hundred seconds led to a final state displaying a 0°d ynamic receding contact angle. This effect was absent in the case of 2-propanol, where the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…It is found that Marangoni stresses increase the rate at which the dynamic contact angle in our geometry increases with Dynamic wetting failure in surfactant solutions 305 contact-line speed, consistent with experimental observations of the behaviour of receding contact angles in surfactant solutions (Fell et al 2011Anyfantakis et al 2012). The hydrodynamic model shows that 2D steady wetting fails at a critical substrate speed corresponding to a critical capillary number Ca crit .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is found that Marangoni stresses increase the rate at which the dynamic contact angle in our geometry increases with Dynamic wetting failure in surfactant solutions 305 contact-line speed, consistent with experimental observations of the behaviour of receding contact angles in surfactant solutions (Fell et al 2011Anyfantakis et al 2012). The hydrodynamic model shows that 2D steady wetting fails at a critical substrate speed corresponding to a critical capillary number Ca crit .…”
Section: Resultssupporting
confidence: 90%
“…Figure 7 at which θ M increases with Ca. This is consistent with experimental observations of receding contact angles that decrease more quickly with contact-line speed when surfactant is present (Fell et al 2011Anyfantakis et al 2012). Figure 7(b,c) shows that interface deformation primarily occurs near the dynamic contact line as the interface elongates, which confirms the formation of a thin-film wedge in the receding phase (Kistler 1993;Marchand et al 2012).…”
Section: Influence Of Surfactants On Wetting Failuresupporting
confidence: 87%
“…2B). 61 A glass beaker containing milli-Q water was placed on a translation stage. The beaker was connected to a capillary (inner diameter 855 mm) through a tubing system and a metering valve.…”
Section: Microtubing Setupmentioning
confidence: 99%
“…This procedure was found to provide clean surfaces, an essential requirement for reproducible results. 61…”
Section: Microtubing Setupmentioning
confidence: 99%